The Characterization of Haemaglutinin Protein of Vili Vibrio alginolyticus as Adhesion Molecule on Epithelial Cells Receptor of Humpback Grouper (Cromileptes altivelis) - Yanuhar, Uun (Universitas Syiah Kuala, 2008)
Vibriosis was a crucial problem and a primer infection causing mortality of humpback grouper.Virulence factor of vibrio, such as vili, is an adhesion molecule protein based on haemaglutination test toblood serum of humpback grouper. This research was aimed to characterize an adhesion molecule of viliprotein of V. alginolyticus on epithelial cells of Humpback grouper as haemaglutinin protein. Themethods are laboratory exploration by isolate epithelial cells of Humpback grouper, characterize a receptorand test vili protein to adhesion molecule that is epithelial cell of Humpback grouper. The result of proteinhaemaglutinin test to vili V. alginolyticus show that an adhesion molecule with a molecule weight of38.98 kDa is an adhesin vili V. alginolyticus and a haemaglutinin. The adhesion pattern of V.alginolyticus on epithelial cells of Humpback grouper exposed to protein haemaglutinin of vili show bothdiffuse and localize pattern. Research conclusion was the haemaglutinin protein of vili V. alginolyticuswas an adhesin having a role to both virulence process of bacteria and attachment process to receptor ofepithelial cells of Humpback grouper.Keywords: adhesion molecule, epithelial cell, vili, V. alginolyticus, C. altivelis